A fly in the soup? The role of ambiguity in student assessment. Issue 3 (November 2022) - Endres, Megan L.; Milner, Morgan; Camp, Richaurd R.
Abstract: Accurate assessment of student learning goals is challenging because situational or individual characteristics can give some students a disproportionate advantage that is not due to their knowledge and skills. Many assessments have elements of uncertainty, novelty, and ambiguity, and in these situations, students with a higher tolerance of ambiguity (TA) may perform better. Because ambiguity can be unavoidable in assessment, we asked if trust mitigates negative effects for students who cannot tolerate ambiguity well. We conducted an assessment activity with 101 students in 24 teams to judge attainment of AACSB (Association to Advance Collegiate Schools of Business) learning goals for accreditation. We manipulated the activity to have either high or low levels of ambiguity. Affective trust moderated relationships between TA and two outcomes—self-efficacy and knowledge sharing. High affective trust compensated for low TA in a highly ambiguous task, but cognitive trust did not. These results suggest that ambiguity is a potential source of criterion contamination when assessing students in groups and that affective trust can play an important role in reducing negative effects. We present implications for classroom practices, student assessment, and future research. Highlights: Ambiguity is a potential source of criterion contamination in student assessment. Students with high ambiguity tolerance may benefit from ambiguity in assessment. Affective trust mitigates negative effects of ambiguity in student assessment. Affective trust benefits students with low ambiguity tolerance in assessment.